Integrated Modulation Technique for Switched capacitor Ultra Sparse Matrix converter - Raghuram M.; Chauhan A.K.; Singh S.K. (My University, 2025)
Ultra sparse matrix converter(USMC) is a unidirectional single stage AC-AC converter without DC link capacitor. However it has limited voltage gain. To enhance voltage gain and to achieve wider load power factor range, a switched capacitor USMC (SC-USMC) is being reported recently. Even for unbalanced supply conditions SC-USMC produced balanced output without any additional protection circuitry. By proper placement of switching states voltage gain of SC-USMC and capacitor voltage rating can be improved. This paper addresses these improvements by proposing integrated space vector modulation technique for SC-USMC. Proposed modulation scheme is validated through analysis, simulation and experimental results. © 2018 IEEE.